2015
DOI: 10.2147/dddt.s87064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization, and anticancer activity of a monobenzyltin compound against MCF-7 breast cancer cells

Abstract: A new monoorganotin Schiff base compound, [N-(3,5-dichloro-2-oxidobenzylidene)-4-chlorobenzyhydrazidato](o-methylbenzyl)aquatin(IV) chloride, (compound C1), was synthesized, and its structural features were investigated by spectroscopic techniques and single-crystal X-ray diffractometry. Compound C1 was exposed to several human cancer cell lines, including breast adenocarcinoma cell lines MCF-7 and MDA-MB-231, ovarian adenocarcinoma cell lines Skov3 and Caov3, and prostate cancer cell line PC3, in order to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 35 publications
4
27
0
6
Order By: Relevance
“…The IC 50 value of compound C1 in MDA-MB-231 cells was reported as 2.5 μg/mL in a previous study28. The results of this study indicated that cisplatin inhibited the growth of MDA-MB-231 cells in vitro .…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations
“…The IC 50 value of compound C1 in MDA-MB-231 cells was reported as 2.5 μg/mL in a previous study28. The results of this study indicated that cisplatin inhibited the growth of MDA-MB-231 cells in vitro .…”
Section: Resultssupporting
confidence: 59%
“…9) was discussed in detail in previously published article28. This Schiff base compound was supplied by Dr.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…OSCP concentration that was found to give 50% of cell viability is 50 ± 1.019 µM. DNA ladder formation was also observed after 24 h and 48 h These results come in agreement with previous results reported that OSCP possess anti-proliferation and antimigration capacity of cancer via different signaling pathways [41,42]. To define the mechanism by which OSCP restrict growth and induces apoptosis, we investigated the regulators of these processes including Bcl-2 and Bax.…”
Section: Discussionsupporting
confidence: 89%